The Safety and Efficacy of Tofacitinib in 24 Cases of Pediatric Rheumatic Diseases: Single Centre Experience - Kostik, Mikhail M.; Raupov, Rinat K.; Suspitsin, Evgeny N.; Isupova, Eugenia A.; Gaidar, Ekaterina V.; Gabrusskaya, Tatyana V.; Kaneva, Maria A.; Snegireva, Ludmila S.; Likhacheva, Tatyana S.; Miulkidzhan, Rimma S.; Kosmin, Artem V.; Tumakova, Anastasia V.; et al. (Frontiers in Pediatrics, 2022)
JAK-inhibitors are small molecules blocking the JAK-STAT pathway that have proven effective in the treatment of different immune-mediated diseases in adults and juvenile idiopathic arthritis (JIA). Aim of Study To evaluate the safety and efficacy of tofacitinib in children with different rheumatic diseases. Material and Methods We extracted information from 24 children with the following diagnosis: JIA (n = 15), undifferentiated systemic autoinflammatory diseases (SAIDs) (n = 7), and juvenile dermatomyositis (JDM) (n = 2) who have been treated with tofacitinib for a period of longer than 6 months. The treatment outcomes were classified according to the opinion of the attending physicians as having a complete response (CR), i.e., the absence of disease activity, or a partial response (PR)—a significant improvement of symptoms and disease activity, or no response (NR)—no changes in disease activity. Results CR was achieved in 10/24 patients; 7/15 among JIA patients, 1/2 among JDM patients, 4/7 among SAID patients, and PR in 5/15 of JIA, 1/2 of JDM, and 3/7 of SAID patients. Three non-responders with JIA discontinued tofacitinib. Corticosteroids were successfully tapered off in 11/14 patients and discontinued in 2/14 patients. Four patients had side effects not requiring treatment discontinuation: liver enzyme elevation (n = 2), hypercholesterolemia (n = 1), lymphadenitis (n = 1). Conclusion JAK-inhibitors are effective new therapies for the treatment of multiple immune-mediated diseases. Our experience has shown the best results in patients with JIA and JIA-associated alopecia, and type I interferonopathies. More data from randomized controlled clinical trials are needed to use JAK-inhibitors safely in pediatric rheumatic diseases.